Feedback linearization constrained NMPC for bilinear systems - Bacic, M; Cannon, M; Kouvaritakis, B (2003)
This paper describes a method for calculating invariant/feasible sets with respect to feedback linearizing control law for bilinear systems. The output optimality of a feedback linearizing control law provides a good basis for using such invariant sets in a dual mode MPC settings. © 2003 IEEE.